Bestimmungstabellen für die Gattungen der aquatischen Coleopteren-Larven Mitteleuropas. 22. Beitrag zur Kenntnis der mitteleuropäischen Coleopteren-Larven. - Klausnitzer, Bernhard (Contributions to Entomology = Beiträge zur Entomologie, 1977)
Keys to the families of aquatic Adephaga (Hygrobiidae, Haliplidae, Dytiscidae, Gyrinidae) and Polyphaga (Hydraenidae, Spercheidae, Hydrophilidae, Helodidae, Eubriidae, Dryopidae, Georyssidae, Heteroceridae) are presented. Keys to the genera are given fort the following families: Halipidae, Dytiscidae, Gyrinidae, Hydraenidae, Hydrophilidae, Helodidae and Dryopidae. These keys make it possible to determine a total of 81 genera from the twelve families mentioned above.